2019
DOI: 10.1161/atvbaha.119.312613
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Mitochondrial Oxidative Damage Improves Reendothelialization Capacity of Endothelial Progenitor Cells via SIRT3 (Sirtuin 3)-Enhanced SOD2 (Superoxide Dismutase 2) Deacetylation in Hypertension

Abstract: Objective: Dysfunction of endothelial progenitor cells (EPCs) leads to impaired endothelial repair capacity in patients with hypertension, but the mechanisms remain incompletely understood. Mitochondrial oxidative stress is involved in endothelial injury in hypertension. In this study, we aim to investigate the role of mitochondrial oxidative stress in the deficient endothelial reparative capacity of EPCs and identify enhanced SIRT3 (sirtuin 3)-mediated SOD2 (superoxide dismutase 2) deacetylation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 69 publications
3
34
0
Order By: Relevance
“…The role of the activation of NF-κB mediated signal transduction and of an enhanced mitochondrial oxidative stress at different stages of atherosclerosis, beginning from plaque formation to its destabilization and rupture, is well known. 29,30 Interestingly, our "in vitro" data showed that in endothelial cells, hyperglycemia evoked a significant demethylation in CpG islands located in promoter region of NF-κB and SOD2. In agreement with DNA methylation modification, HG exposure induced a TET2 upregulation and an increase of NF-κB and NFKB target gene expression.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The role of the activation of NF-κB mediated signal transduction and of an enhanced mitochondrial oxidative stress at different stages of atherosclerosis, beginning from plaque formation to its destabilization and rupture, is well known. 29,30 Interestingly, our "in vitro" data showed that in endothelial cells, hyperglycemia evoked a significant demethylation in CpG islands located in promoter region of NF-κB and SOD2. In agreement with DNA methylation modification, HG exposure induced a TET2 upregulation and an increase of NF-κB and NFKB target gene expression.…”
Section: Discussionmentioning
confidence: 86%
“…Thus, to better clarify, the potential role of incretin‐based treatment in preventing and/or reverting the DNA methylation changes induced by HG, the effects of GLP‐1 or exenatide on DNMTs and TET2 expression and DNA methylation of NF‐κB and SOD2 has been evaluated in aortic endothelial cells exposed to high glucose for 7 days and co‐treated with GLP‐1 or exenatide. The role of the activation of NF‐κB mediated signal transduction and of an enhanced mitochondrial oxidative stress at different stages of atherosclerosis, beginning from plaque formation to its destabilization and rupture, is well known 29,30 …”
Section: Discussionmentioning
confidence: 99%
“…4 A), and this increase was associated with significant downregulation of the antioxidant proteins Gpx1, HO-1, and SOD2, as well as the deacetylase SIRT3 ( Fig. 4 B) [ 29 ]. Additionally, we showed that not just the expression but also the activity of SOD2 was significantly inhibited in Mel-SHK-treated HeLa cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, SIRT3 can protect endothelial cells from mitochondrial ROS damage and increase NO release to benefit vasodilatation 159 . Moreover, SIRT3-mediated SOD2 deacetylation also contributes to maintaining the escape of endothelial progenitor cells (EPCs) from dysfunction and injury as well as decreased vascular inflammation 161 , 162 . Maternal obesity is another key problem in human beings.…”
Section: Sirt3 and Human Diseasementioning
confidence: 99%